Coronal alignment does not enable to predict the degree of femoral and tibial torsion - Leonard Grünwald; Sophie Schmidt; Marc‐Daniel Ahrend; Tina Histing; Stefan Döbele (Journal of Experimental Orthopaedics)
Abstract Purpose Malalignment of the lower extremity can affect one, two or all three anatomic planes. We hypothesized an influence between the malalignment of the coronal and axial planes. Methods A total of 356 lower extremities of 226 patients were included. Femoral and tibial torsion were assessed in computer tomographic scans while frontal plane alignment was measured in long‐leg standing radiographs. The mechanical angles were for knee phenotyping according to the coronal plane alignment of the knee classification. The correlation between the coronal alignment and torsional profile was analyzed. The population was divided into three groups according to leg alignment (valgus, neutral, varus) and gender. Results As the coronal alignment changed from valgus to varus the tibial external torsion increased (r = 0.35; p < 0.001). Femoral internal torsion increased as well but only in the male subgroup (r = −0.34; p < 0.001). Both femoral internal torsion and tibial external torsion increased with higher mechanical lateral distal femoral angle (mLDFA) but were not related to mechanical medial proximal tibial angle. A distinct pattern of results concerning knee phenotypes in relation to femoral and tibial torsion was found. Conclusion Tibial torsion correlated with increasing varus alignment while both femoral and tibial torsion correlated with higher mLDFA, but the correlations were weak. Therefore, the coronal alignment does not enable to predict the degree of femoral and tibial torsion. This study demonstrates that an individual approach to each patient with lower limb malalignment is unavoidable. Level of Evidence Level III.